Fine-scale spatial segregation in a pelagic seabird driven by differential use of tidewater glacier fronts - Bertrand, Philip; Bêty, Joël; Yoccoz, Nigel G.; Fortin, Marie-Josée; Strøm, Hallvard; Steen, Harald; Kohler, Jack; Harris, Stephanie M.; Patrick, Samantha C.; Chastel, Olivier; Blévin, P.; Hop, Haakon; et al. (Scientific Reports, 2021)
In colonially breeding marine predators, individual movements and colonial segregation are influenced by seascape characteristics. Tidewater glacier fronts are important features of the Arctic seascape and are often described as foraging hotspots. Albeit their documented importance for wildlife, little is known about their structuring effect on Arctic predator movements and space use. In this study, we tested the hypothesis that tidewater glacier fronts can influence marine bird foraging patterns and drive spatial segregation among adjacent colonies. We analysed movements of black-legged kittiwakes (Rissa tridactyla) in a glacial fjord by tracking breeding individuals from five colonies. Although breeding kittiwakes were observed to travel up to ca. 280 km from the colony, individuals were more likely to use glacier fronts located closer to their colony and rarely used glacier fronts located farther away than 18 km. Such variation in the use of glacier fronts created fine-scale spatial segregation among the four closest (ca. 7 km distance on average) kittiwake colonies. Overall, our results support the hypothesis that spatially predictable foraging patches like glacier fronts can have strong structuring effects on predator movements and can modulate the magnitude of intercolonial spatial segregation in central-place foragers.